2023
DOI: 10.1080/07853890.2023.2267083
|View full text |Cite
|
Sign up to set email alerts
|

Exercise-based rehabilitation in and with nature: a scoping review mapping available interventions

Henriette Busk,
Jonas Ahler,
Alessio Bricca
et al.

Abstract: Introduction Exercise is an effective component in rehabilitation of a range of chronic conditions. There is a growing interest in the use of exercise-based nature interacted rehabilitation (EBNIR), but an overview of current evidence is missing. The objective of this scoping review was to map existing exercise-based rehabilitation interventions conducted with incidental or intentional nature interaction focusing on its populations, types of outcomes, and theoretical rationale for people with phys… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 59 publications
(151 reference statements)
0
0
0
Order By: Relevance
“…In addition, it prevents several serious illnesses, including osteoporosis, and vitamin D insufficiency. Therefore, improving accessibility to outside nature enhances engaging in physical activity and exercise, which has a great impact on quality of life and general health and wellbeing ( Busk et al, 2023 ; Manferdelli et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, it prevents several serious illnesses, including osteoporosis, and vitamin D insufficiency. Therefore, improving accessibility to outside nature enhances engaging in physical activity and exercise, which has a great impact on quality of life and general health and wellbeing ( Busk et al, 2023 ; Manferdelli et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, studies have demonstrated that the efforts required to overcome the challenges faced during uphill and downhill walking are correlated with enhanced cardiovascular health [3,4], increased muscle activation [7,8], and the management of chronic conditions like diabetes [6], obesity [5], COPD [13] and osteoarthritis [66]. In addition, healthcare professionals, including physical therapists and rehabilitation specialists, can utilize spatiotemporal parameters to adjust and optimize rehabilitation programs [28,29] by improving certain functional abilities (e.g., muscle strength) or identifying specific gait abnormalities and tracking changes over time. Understanding ground reaction force and GRF patterns may also facilitate the implementation of intervention programs to improve weight distribution and reduce joint stress, thus alleviating asymmetries or excessive joint loading.…”
Section: Discussionmentioning
confidence: 99%
“…where W = walking speed and S = slope of the terrain Knowing the effects of hiking speeds and terrain's slopes interplay on gait kinematics, and kinetics is essential for promoting safety [24,25], optimizing performance, designing appropriate trails [26], and equipment (e.g., footwear [27]), enhancing recreation and fitness experiences, supporting rehabilitation [28,29], and minimizing environmental impact [30]. This information may also be valuable to individuals who, either because they face limited access to physical environments or want to diversify their exercise routines, prefer to exercise in controlled indoor conditions using a treadmill.…”
Section: Introductionmentioning
confidence: 99%